Protection Of Persons With Disabilities In Times Of Armed Conflict - نور داود محمد; ماهر ملندي (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Persons with disabilities are among the most affected groups in society by the violence and conflicts arising from armed disputes between warring parties, and the resulting negative impacts on the economic and social situation within conflict zones. This is due to their inability to protect themselves from the dangers of war and the likelihood of being forcibly displaced, which often leads to separation from their families or caregivers. Additionally, persons with disabilities become more vulnerable to social marginalization and discrimination based on their disabilities in such situations, significantly affecting their living conditions and exacerbating their suffering, which is mainly related to the circumstances and challenges of disability. Therefore, it is essential to have international legal rules that provide effective protection for persons with disabilities and ensure the continuous enjoyment of their fundamental rights during armed conflicts. The international community has recognized the extent of the challenges and difficulties faced by these individuals in conflict zones and the necessity of not merely protecting them through the general principles of international humanitarian law.